Cardiovascular risk factors for stroke among the elderly - Stojanovski Nataša; Tomić Aleksandra; Radojičić Aleksandra; Mijajlović Milija (Medicinski Podmladak)
By the year 2050 there will be around 426 million people over 80 years of age. As lifespan is extended, cardiovascular risk factors are becoming one of many challenges. Cardiovascular diseases are the leading cause of death at the age over 65. Stroke is also one of the leading causes of disability and mortality. It is estimated that 75% of strokes occur in people over 65 years of age. Understanding how to manage modifiable risk factors for stroke and recognizing the influence of non-modifiable risk factors is crucial. Age is a leading factor in a non-modifiable group of stroke risk factors. Gender is also highlighted due to socioeconomic and biological differences between men and women. Modifiable risk factors for stroke are diabetes mellitus (DM), obesity, psychosocial factors, dyslipidemia, smoking, physical inactivity, diet, alcohol intake, high blood pressure and other cardiovascular diseases like atrial fibrillation (AF), with hypertension being one of the most important risk factors in the group of elderly patients. Knowing more about the associations of these risk factors with stroke in different age groups can help with better management and stroke prevention.